Cloud computing migration barriers and advantages in manufacturing – an analysis of ambiguity and dependences in the assessment criteria - Bartkiewicz, Halina; Gontar, Zbigniew (Bariery i korzyści migracji do chmuryobliczeniowej w przedsiębiorstwach przemysłowych – analiza niejednoznaczności i związków między kryteriami oceny, 2018)
There is still many misunderstandings associated with the assessment of the barriers encountered in the process of IT solutions migration to the computational cloud and the benefits to be expected. The purpose of this paper is to organize the criteria used in this field, to analyze the dependencies between them. This will allow us to better understand the problem of migration to the cloud and to improve the decision-making processes related to it. A comprehensive survey was carried out, covering about 400 manufacturing enterprises in Poland using cloud-based IT solutions in various areas. The elements of the study were questions about the barriers and benefits encountered in this process. The paper analyzes the relationships between the obtained categories using diverse data mining methods: association rules mining and hierarchical agglomerative clustering. The obtained results allow to identify the conceptual structure and build a model of relationships inside the problem
Econometrics = Ekonometria, 2018, Vol. 22, No. 3, s. 41-54
Keywords: cloud computing; association mining; similarity based semantic clustering; chmura obliczeniowa; eksploracja reguł asocjacyjnych; grupowanie semantyczne oparte na podobieństwie